Approaching Ideologies of Things Made of Language : A Case Study of a Finno-Karelian Incantation Technology - Frog, Mr. (Фолклористика : часопис Удружења фолклориста Србије, 2021)
This article introduces an approach to ideologies of texts and of categories of text type for approaching the emic conceptions of things made of language or other kinds of signs. Finno-Karelian incantations of the ritual specialist known as a tietäjä provide a case study, considered in the broader context of cultures in the Circum-Baltic region. Text ideology is salient in this tradition owing to a conception that a performer will lose an incantation’s power when it is communicated as a whole to someone else, but not if verses are omitted. Discussion is organized in four parts, providing different types of contextualization before discussing emic conceptions of incantations proper. It begins with a theoretical introduction to text ideologies and genre ideologies in relation to language ideologies. This section includes positioning the approach from the perspective of (Finnish) folklore studies for better multidisciplinary accessibility. The second section contextualizes the tietäjä as a social institution, the corpora and approach. The third section introduces the ritual technology of the tietäjä, the physics of the world in which these operate and what these are conceived as ‘doing’ in ritual performance. The fourth section turns to the understanding of incantations as a type of text object in relation to the technology and their variation in practice. Peer reviewed